A novel homozygous splice‐site mutation in RYR1 causes fetal hydrops and affects skeletal and smooth muscle development. (13th June 2017) - Meier, Nicole; Bruder, Elisabeth; Filges, Isabel
Abstract : What's already known about this topic? Mutations in the RYR1 gene can cause variable phenotypes including autosomal dominant malignant hyperthermia, multi‐minicore disease, core‐rod myopathy and autosomal recessive lethal multiple pterygium syndrome at the severe end of the spectrum. What does this study add? Autosomal recessive mutations in RYR1 cause non‐immune fetal hydrops more often than previously thought. These mutations affect skeletal muscle development but also impact smooth muscle tissue in early human development. RYR1 should be added to sequencing panels in prenatal diagnostics.